PERANCANGAN KURSI ERGONOMIS UNTUK MEMPERBAIKI POSISI KERJA PADA PROSES PACKAGING JENANG KUDUS - Akh Sokhibi (JURNAL REKAYASA SISTEM INDUSTRI, 2017)
Jenang is one of the special food from the Kudus City of Central Java Province. The process of making jenang through several stages, namely the process of material insertion, the process of mixing the material while cooked with the mix, the process of printing in a baking sheet and packaging process. In the process of this jenang packaging is done by workers who sit on a wooden chair with no foam pads and no back support. Sitting position, judging from the aspect of ergonomics sitting position is less comfortable. Therefore, it is necessary to design seats for ergonomic jenang packaging operators. The method used in designing this chair is by descriptive analysis, with the seat dimension approach to anthropometry of worker's body. Required data include anthropometric data of workers' packaging body dimensions and data obtained from existing research. Then the data is processed to be applied to the design. This design is a prototype that will be measured and applied to the packaging hood of the worker. The purpose of this research is applying ergonomic chair to jenang packaging worker, so it is expected to improve work position of jenang packaging worker and reduce discomfort that can cause fatigue. The result of the research shows that with the application of ergonomic chair design to the jenang packaging worker, there is improvement of work position on the jenang packaging worker and decrease the level of discomfort that happened to the neck, back, round, buttock and elbow of the jenang packaging worker.